2022
DOI: 10.1167/iovs.63.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Timed Notch Inhibition Drives Photoreceptor Fate Specification in Human Retinal Organoids

Abstract: Purpose Transplanting photoreceptors from human pluripotent stem cell–derived retinal organoids have the potential to reverse vision loss in affected individuals. However, transplantable photoreceptors are only a subset of all cells in the organoids. Hence, the goal of our current study was to accelerate and synchronize photoreceptor differentiation in retinal organoids by inhibiting the Notch signaling pathway at different developmental time-points using a small molecule, PF-03084014 (PF). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
(87 reference statements)
1
8
1
Order By: Relevance
“…It is also intriguing that inhibition of Notch signaling enables the generation of OTX2 + neurons. The bias toward the OTX2 lineage after Notch signaling inhibition has already been described in previous studies ( Chew et al., 2022 ; Finkbeiner et al., 2022 ; Jadhav et al., 2006 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is also intriguing that inhibition of Notch signaling enables the generation of OTX2 + neurons. The bias toward the OTX2 lineage after Notch signaling inhibition has already been described in previous studies ( Chew et al., 2022 ; Finkbeiner et al., 2022 ; Jadhav et al., 2006 ).…”
Section: Discussionsupporting
confidence: 79%
“…For this reason, we carried out a similar reprograming experiment to those described above using RS-derived MG. To ensure the MG cultures did not contain any progenitors, RS were treated with a gamma secretase inhibitor (PF4014) for 3 days prior to dissociation of the MG in two-dimensional (2D) cultures. Previous studies have shown that inhibition of the Notch signaling pathway rapidly induces the differentiation of MPC ( Chew et al., 2022 ; Kaufman et al., 2019 ; Nelson et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…An hiPSC line with GFP knocked in at the AAVS1 safe harbor locus was differentiated into cone-rich 3D-retinal organoids ( Figures S1 A–S1C) ( Pei et al., 2015 ). The 60-day-old organoids were briefly pulsed (24 h) with a Notch inhibitor (PF-03084014) to drive the fate into cone differentiation and reduce the proliferative stem cell population, as previously described ( Chew et al., 2022 ). 13-LGS retinas were damaged at least 2 weeks pretransplantation through either chemical insult or mechanical detachment ( Figures S2 A–S2C).…”
Section: Resultsmentioning
confidence: 99%
“…At the end of 4 weeks, the optic vesicles were manually excised and cultured in a 3D-RDM with 1 μM ATRA (R2625, Sigma-Aldrich, St. Louis, MO) to generate self-assembled laminated 3D-retinal organoids. Approximately 55- to 60-day-old organoids were treated with 10 μM PF-03084014 hydrobromide (PF) (PZ0298, Sigma-Aldrich), a small-molecule inhibitor of the Notch pathway for 24 h. The purpose of using PF was to drive the differentiation of the remaining retinal progenitor pool within the 3D-retinal organoids toward the cone fate ( Chew et al., 2022 ). PF media was removed and viable cone-rich 3D-organoids expressing the parental reporter GFP were then collected in a 15-mL conical tube filled with freshly prepared 3D-RDM containing ATRA.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas Rxrg emerged as a candidate interactor from the RNA sequencing data of the orJ and orJ;mi het mutants, our interest in GS activity arose from a prediction that inhibiting Notch signaling would accelerate the onset of neurogenesis in the orJ retina, a hypothesis based on prior knowledge of the function of Notch signaling and pharmacological GS inhibition in the embryonic retina and more recently in human retinal organoids 84 . Although toxicity issues precluded us from testing this hypothesis, we found that GS inhibition with a low dose of DBZ further reduced RPC proliferation in orJ RPCs.…”
Section: Discussionmentioning
confidence: 99%